Determination of double-K fracture parameters using semi-circular bend test specimens. (February 2016) - Xu, Shilang; Malik, Muhammad Akbar; Li, Qinghua; Wu, Yao
Highlights: Double- K fracture parameters were determined using semi-circular bend test specimen. Fracture parameters i.e. critical crack length and CMOD were calculated in detail. The value of effective crack length was found to increase with the specimen size. Abstract: The present research was conducted to evaluate the double- K fracture parameters using semi-circular bend test. Fracture tests were carried out on semi-circular bend specimens with three different diameters with a range from 200 mm to 500 mm and four different concrete strengths. The results indicated that double- K fracture parameters K Ic ini and K Ic un values for semi-circular bend specimens were size and strength dependent. All the fracture parameters such as critical effective crack length, critical crack mouth opening displacement and unstable fracture toughness increased as the specimen size increased; while, initial fracture toughness decreased with the increase of specimen size.